An Analysis of the Role and Effects of Tourism Attraction in Urban Identity: Case Study in Charikar City) - Parwiz Qaderi; Samiullah Aman; Abdul Monir Rahimi (Penerbit Hellow Pustaka, 2025)
Tourism attractions play a key role in shaping and strengthening the urban identity of the Charikar city. With its rich history and diverse culture, this city features attractions that not only draw tourists but also provide residents with a sense of belonging and identity. Historical monuments, local markets, and cultural spaces are among the essential elements that form urban identity and foster social interactions. Likewise, natural and cultural attractions can serve as instruments to promote public awareness about the importance of protecting the environment and preserving local culture. Finally, attention to tourist attractions can help create a positive image of the Charikar city at the national and international levels, and lead to attracting increased investment in the city. The overall objective of this study is to identify and explore the role of tourist attractions in the urban identity of the Charikar city. The research method is based on the collection of quantitative data, and using field methods to obtain statistical insights, questionnaire distribution has been conducted. To assess reliability, the Cronbach's alpha test was applied, yielding a Cronbach's alpha coefficient of 0.707, which falls within the acceptable range. The statistical population for this study consists of university professors, students, and cultural activists. The sample size comprises 50 individuals, and the data were analysed using descriptive and analytical methods. As a result of the research, we founded that tourist attractions are instrumental in the urban identity of the Charikar city.